Longhorn beetles in lesser spotted woodpecker habitat : a pheromone-based inventory of longhorn beetles in southern Sweden - Celander, Patrik Jonas Krister (SLU/Dept. of Plant Protection Biology, 2020)
The understanding of species’ ecology and their trophic interactions, are crucial in the work of conservation. A population decline in a predatory species may be a result of a decline in their food source, a trophic level down. Then an understanding of why the predator’s food source has declined is needed, to be able to pinpoint conservation actions. In Swedish forests one such trophic interaction is between dead wood, saproxylic insects and woodpeckers. Modern forestry of clear cuttings and monoculture plantations of coniferous trees, has changed many Swedish forests to be less diverse in tree species, age classes of trees, types of dead wood, denser and hence also deficits in dead deciduous wood. As a result, insects in Swedish forests have declined. Most longhorn beetle species (Cerambycidae) larvae are saproxylic and have different niches. Niches such as specific host trees, age classes of trees, types of wood and different succession stages of decomposed dead wood. Of the 118 species of longhorn beetles in Sweden, 46 were red listed in the 2020 Swedish red list evaluation. Lesser spotted woodpecker (Dryobates minor) is a small woodpecker preferring open broadleaf forests. Between 1975-1991 the Swedish population decreased by approximately 50% and today D. minor is classified as Near Threatened, according to the 2020 Swedish red list evaluation. Studies in southern Sweden have shown that the most important factor influencing reproduction success in D. minor is the prey density several weeks to months before breeding. During that time they feed on wood living insect larvae, mainly in dead thin twigs on living deciduous trees. Longhorn beetle larvae and pupae are probably the most important food source. In order to understand why D. minor is threatened, their food source has to be understood as well. In this study I used pheromone traps to monitor longhorn beetles in 34 areas between May-July, in the counties of Skåne, Blekinge, Småland and Västergötland in southern Sweden. Pheromone-based trapping is an effective method to monitor otherwise elusive species and in this study pheromone blends attracting mainly Pyrrhidium sanguineum, Phymatodes testaceus, Poecilium alni and Plagionotus arcuatus were used. The areas monitored in this study, had been inventoried 2019-2020 by “project lesser spotted woodpecker at Lund University”, giving occurrence information about D. minor. In this study I found no differences in longhorn beetle abundance or longhorn beetle biodiversity between areas inhabited or uninhabited by D. minor. Hence, no evidence was found that D. minor habitat choice depend on the longhorn beetles studied. A strong positive association was, however, seen between P. sanguineum and P. alni and large dissimilarities between P. testaceus and P. alni as well as between P. sanguineum and Anaglyptus mysticus. These associations between the species could perhaps be used in future identification of indicator species. I also found a negative correlation between the biodiversity of longhorn beetles and increasing latitudes, but the factors affecting longhorn beetles are not clear. Lastly, several new localities with red listed species were found and my findings suggest that P. sanguineum, P. alni and perhaps also A. mysticus distributions are underestimated.